2016
DOI: 10.1007/s11695-016-2274-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gastric Volume and Their Implications for Weight Loss after Laparoscopic Sleeve Gastrectomy

Abstract: The volume of the gastric remnant increased significantly during the first year after LSG. However, this increase was not associated with weight loss. Further prospective research with longer follow-up periods is needed to confirm or contrast the present results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 34 publications
2
15
0
1
Order By: Relevance
“…Alternatively it could be related to sleeve dilatation. Two recent studies using gastric volumetry with either 3D gastric computed tomography or radiology concluded that some degree of sleeve dilatation occurred in a majority of patients, but that the degree of dilatation was not correlated with food intake and percent weight loss [33, 34]. Interestingly, this is also what we find in our mouse model – no correlation of two-dimensional sleeve surface area with weight loss and weight regain.…”
Section: Discussionsupporting
confidence: 59%
“…Alternatively it could be related to sleeve dilatation. Two recent studies using gastric volumetry with either 3D gastric computed tomography or radiology concluded that some degree of sleeve dilatation occurred in a majority of patients, but that the degree of dilatation was not correlated with food intake and percent weight loss [33, 34]. Interestingly, this is also what we find in our mouse model – no correlation of two-dimensional sleeve surface area with weight loss and weight regain.…”
Section: Discussionsupporting
confidence: 59%
“…In the center, as mentioned above, we found two opposite factors for the regulation of food intake. A recent study has shown that a residual stomach expansion occurred in more than 50% of the SG patients over a short-term period[ 39 , 40 ]. Increased food intake may be the most important factor for the residual stomach expansion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we examined how the results of each analysis changed if we removed follow-up censoring due to switching to a different procedure. Finally, because the SG technique evolved rapidly during the study period (26, 27), we examined whether 1-year weight loss for SG patients differed by year of surgery.…”
Section: Methodsmentioning
confidence: 99%